A new subterranean and troglomorphic species of the genus Oncopodura Carl & Lebedinsky, 1905 (Hexapoda, Collembola) from Samegrelo karst region in Georgia - Mayvan, Mahmood Mehrafrooz; Barjadze, Shalva; Maghradze, Eter; Kováč, Ľubomír (Zootaxa, 2025)
A new species of the genus Oncopodura Carl & Lebedinsky, 1905 is described from a deep, aphotic section of the Jortsku Cave, Samegrelo Province in Georgia. Oncopodura ochokochi sp. nov. is characteristic by the following morphological traits: (1) PAO with 1 simple lobe, (2) basal lamella of unguis longer than half of its length, (3) dorsal side of manubrium with 11+11 ciliated setae and 4+4 smooth macrosetae, (4) dens at basal part with 1 dorsointernal hook, 3 dorsointernal and 2 dorsoexternal ciliated macrosetae, (5) dens at distal part with 1 dorsoexternal and 1 dorsointernal hook, 1 dorsoexternal and 1 dorsointernal ciliated macroseta, and (6) mucro with 4 teeth and 2 basal scales. The species shows a medium level of troglomorphy, i.e. complex of morphological adaptations to a deep subterranean environment. A table with diagnostic characters of European Oncopodura species with a simple lobe in PAO and an updated key to European species are provided.